Cytokine/chemokine transcript profiles reflect mucosal inflammation in Crohn's disease - Stallmach, Andreas; Giese, Thomas; Schmidt, Carsten; Ludwig, Bianca; Mueller-Molaian, Ina; Meuer, Stefan (International journal of colorectal disease, 2003)
BACKGROUND AND AIMS: Immunoregulatory properties of cytokines may contribute to pathological immune reactions in inflammatory bowel disease. There is an urgent need for a simple and dependable means for quantitating inflammatory activity in mucosal biopsies and assessing relapse risk particularly in patients with active Crohn's disease (CD). PATIENTS AND METHODS: Cytokine and chemokine transcripts were quantified using real-time PCR in mucosal biopsy specimens from 70 patients with active inflammatory bowel disease (CD, n=45; ulcerative colitis n=25) and 16 patients with specific colitis (ischemic colitis, infectious colitis). Controls were 12 patients with noninflammatory conditions. CD patients with steroid-induced remission (n=20) were followed for up to 12 months. RESULTS: Compared to not-inflamed mucosa the vast majority of active CD tissue samples expressed significantly elevated transcript levels of IL-1beta, IL-8, IL-23, MRP-14, MIP2alpha, and MMP-1. Moreover, increased cytokine transcript levels were detected in both active ulcerative colitis and specific colitis. Importantly, TNF-alpha, IFN-gamma, CD40L, and IL-23 transcripts increased in active CD only. Transcript levels (MRP-14, IL-8, MMP-1, MIP2alpha) were correlated with clinical disease activity (CDAI) and endoscopic scoring indices. Medical treatment induced stable remission in 14 of 20 patients which was paralleled by a reduction in increased transcript levels. All six patients without normalization of MIP2alpha, MRP-14, TNF-alpha, and IL-1beta transcripts developed an early relapse (n=5) or chronic activity (n=1) during follow-up. CONCLUSION: Elevated proinflammatory cytokine transcripts in active CD may underlie disease reactivation and chronicity. Real-time PCR quantification is a simple and objective method for grading inflammation of intestinal mucosa and may be useful in identifying patients who would benefit from anti-inflammatory remission maintenance.